SLC11A1 associated with tumor microenvironment is a potential biomarker of prognosis and immunotherapy efficacy for colorectal cancer - Ma, Yiming; Zhan, Lei; Yang, Jun; Zhang, Jingdong (Frontiers in Pharmacology, 2022)
Background: Colorectal cancer (CRC) is one of the most lethal digestive system cancers. Tumor microenvironment (TME) plays a central role in the initiation and development of CRC. However, little is known about the modulation mechanism of TME in CRC. Methods: In our study, we tried to identify a biomarker related with TME modulation, which could serve as a potential prognostic biomarker for CRC. We identified differentially expressed genes (DEGs) between ImmuneScore high/low groups and StromalScore high/low groups, respectively. With univariate COX regression analysis and hub gene analysis (cytoHubba), SLC11A1 was identified as the only candidate gene for subsequent analyses. Analyses of CIBERSORT, EPIC, MCPcounter and immunogenic cell death (ICD) were further performed to evaluate effect of SLC11A1 on TME. We also collected samples and performed Real-time quantitative PCR (RTq-PCR) to verify the expression levels of SLC11A1 in CRC and adjacent normal tissues. The imvigor210 cohort, TIDE score and IPS were used to analyze the association between SLC11A1 and immunotherapy efficacy. Results: SLC11A1 was highly expressed in CRC compared with normal colorectal tissues, and it was associated with poor prognosis and advanced clinicopathological stages. The results of gene set enrichment analysis (GSEA) showed that TGF-β pathways, JAK STAT pathways and angiogenesis were significantly enriched in high-SLC11A1 group. Single-cell analysis validated the correlation between SLC11A1 and TME. By CIBERSORT, EPIC and MCPcounter algorithms, we found that there was more macrophages and fibroblasts infiltration in SLC11A1 high expression group. Meanwhile, high-SLC11A1 patients had lower IPS scores, higher TIDE scores and less immunotherapy benefits, compared with low-SLC11A1 patients. Conclusions: In conclusion, SLC11A1 modulating TME could serve as a potential biomarker for poor prognosis and immunotherapy efficacy in CRC.